Caracterização fenotípica e potencial de enraizamento por estaquia de um germoplasma de erva-mate de origem seminal - Tres, Laura (2016)
The genetic divergence provides useful information for the characterization, conservation and use of genetic resources and therefore, the cloning for cuttings is a technique which can o rescuenative materials as well as enabling the implementation of more uniform and productive yerba mate plantations. The objective of this research was to evaluate the genetic divergence between yerba mate genotypes multiplied by seed, by using multivariate analysis, and the potential propagation of genotypes through cuttings. Two studies were performed. On the first one evaluated the genetic divergence of thirty plants (genotypes) selected from a commercial yerba mate plantation in Mato Castelhano municipality in RS, through the characters of branches and leaves. The genetic divergence was evaluated by main component analysis and the average linkage cluster analysis between groups (in Portuguese- UPGMA) and Tocher, using the average euclidean distance as dissimilarity measure. One also obtained the relative contribution of characters for this divergence. On the second study we found the potential for cutting propagationofgenotypes. The cuttingwas carried out from January to May, with the application of 8.000 mg L-1indole butyric acid (IBA). The performance of both groups by UPGMA and Tocher promoted the formation of these 12 groups, with the same genotype distribution forming each group, demonstrating variability in yerba mate germplasm. The characters that most contributed to the genetic divergence were fresh leaf matter, number of leaves per meter of branch and length of the leaf. The retention capacity of the leaves in the cuttings positively influenced the survival and rooting. Rooting was significantly higher in 50% of the genotypes, ranging from 43.8% to 85.4%, demonstrating the potential to be used as donor plant in a cloning seedling production program